COVID-19 immunity (or vaccine) passports: a documentary overview and analysis of regimes of health verification within the coronavirus pandemic - Kosciejew, Marc Richard Hugh (Journal of documentation, 2022)
PurposeIntroducing immunity or vaccine passports is one non-pharmaceutical intervention that governments are considering to exempt immune, vaccinated or otherwise risk-free individuals from lockdowns and other public health restrictions during the coronavirus pandemic. The primary objective of these documents would be to begin reopening societies, restarting economies and returning to a pre-pandemic normalcy. This article aims to present the start of a conceptual documentary analysis of (proposed and existing) COVID-19 immunity passports in order to more fully center their documentary status within research, considerations and conversations about their potential roles, impacts and implications.Design/methodology/approachInspired by Paula A. Treichler's argument for the importance of theoretical thought for untangling the socio-cultural phenomena of epidemics, and drawing upon interdisciplinary theories of documentation, identity and public health, combined with recent news coverage of the coronavirus pandemic, this article provides a contemporary overview and conceptual analysis of emerging documentary regimes of COVID-19 immunity verification involving immunity or vaccine passports.FindingsThree major interconnected objectives could be fulfilled by immunity passports. First, they would establish and materialize an official identity of COVID-19 immune for people possessing the formal document. Second, they would serve as material evidence establishing and verifying individuals' immunity, vaccination or risk-free status from the coronavirus that would, in term, determine and regulate their movements and other privileges. Third, they would create tangible links between individuals and governments' official or recognized identity category of COVID-19 immune. Immunity passports would, therefore, help enable and enforce governmental authority and power by situating individuals within documentary regimes of COVID-19 immunity verification.Research limitations/implicationsIn the expanding interdisciplinary literature on COVID-19 immunity passports, sometimes also called certificates, licenses, or passes, there appears to be only minimal reference to their documentary instantiations, whether physical, digital, and/or hybrid documents. As yet, there is not any specific documentary approach to or analysis of immunity passports as kinds of documentation. A documentary approach helps to illuminate and emphasize the materiality of and ontological considerations concerning the coronavirus pandemic and its associated kinds of immunity or vaccination.Social implicationsBy beginning an exploration of what makes immunity passports thinkable as a public health response to the coronavirus pandemic, this article illuminates these health and identity documents' material implications for, and effects on, individuals and societies. This article, therefore, helps shed light on what immunity passports reveal about the complicated and contested intersections of identity, documentation, public health and socio-political control and discipline.Originality/valueThis article contributes the start of a documentary analysis of (proposed and existing) COVID-19 immunity passports in order to more fully center their documentary status within research and conversations about them.